Identità narrativa e identità traduttiva: due possibili paradigmi per la psicoanalisi? - Martini, Giuseppe; Busacchi, Vinicio (B@belonline, 2021)
The Authors discuss the question of narration and narrative identity starting from the work of Paul Ricœur and illustrate the reception and the application of narration in the psychoanalytic field. Their reflection proceeds towards an enhancement of the third paradigm of Ricœurian hermeneutics: the translation, of which the Autors discuss the possible strengths in a philosophical and psychoanalytic field. A comparison is thus proposed between the interpretation, narration and translation, always referred to psychoanalysis.